IMPLEMENTASI JAMINAN KESEHATAN MASYARAKAT DAERAH BAGI MASYARAKAT MISKIN DI KABUPATEN PELALAWAN (Studi Kasus di Kecamatan Pangkalan Kuras, Kab. Pelalawan) - Dewi, Silfia Kumala (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This research is motivated by the existence of Regional Health Insurance(Jamkesda) which is a health service guarantee program for poor ordisadvantaged people outside the public health insurance quota which is theresponsibility and implemented by the regional government of Pelalawan district.However, there are still poor people who have not registered as regional healthinsurance participants. Therefore, the aim of this thesis research is first, to findout how regional health insurance is implemented for the poor in PelalawanRegency. Second, find out the inhibiting factors in implementing regional healthinsurance for the poor in Pelalawan Regency. Third, to find out what efforts thePelalawan district government has made in implementing regional healthinsurance for the poor.This type of research can be classified into the type of sociologicaljuridical research. This research uses primary data and secondary dataconsisting of primary legal materials, secondary legal materials, tertiary legalmaterials, and data collection techniques.From the results of this research there are three things that can beconcluded. Firstly, with regional health insurance, poor people can obtain healthservices, however, the provision of regional health insurance is not widespreadand is not well targeted. Second, the public's lack of knowledge about existinghealth insurance, as well as limited medical facilities and infrastructure. Third,the efforts made are monitoring, providing guidance and providing regionalhealth insurance that is right on target.Keywords: Implementation, Regional Health Insurance, Poor Communities